Employee performance evaluation using analytic hierarchy process (AHP) for Chemvi Laboratory Sdn. Bhd. - Islam, Rafikul; Periaiah, Nagendran (Creative Decisions Foundation, 2016)
As market becomes more competitive, the management of human capital or retaining high performance employees becomes a major challenge for many organisations. In this regards, evaluation of employee performance is an important activity of human resource managers. The present paper applies AHP to evaluate performance of employees working in Chemvi Laboratory Sdn Bhd, a private Malaysian company. Criteria and subcriteria for the performance evaluation were obtained through group discussion with senior manager of the company Bhd. In fact, five senior managers were interviewed using AHP questionnaires and weight for criteria and subcriteria were evaluated using AHP Calc version 24.12.13 by Klaus D. Goepel. Overall, he management and employees are upbeat with the results obtained via AHP as the criteria and their meanings were clearly defined and communicated to the employees. Employees who performed poorly were also identified and recommendations were made on which criteria that they scored lower and how to improve their performance on those.